2014
DOI: 10.2147/ijgm.s55169
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral responses to innocuous somatic pressure stimulation following aerobic exercise rehabilitation in chronic pain patients: a functional magnetic resonance imaging study

Abstract: Objective The purpose of this research was to assess the functional brain activity and perceptual rating of innocuous somatic pressure stimulation before and after exercise rehabilitation in patients with chronic pain. Materials and methods Eleven chronic pain patients and eight healthy pain-free controls completed 12 weeks of supervised aerobic exercise intervention. Perceptual rating of standardized somatic pressure stimulation (2 kg) on the right anterior mid-thigh a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…The study of Micalos et al (33) did not show any statistically significant pressure-induced brain activity changes following exercise therapy in a sample of chronic musculoskeletal pain patients. Only group by time trends towards activity changes in the superior temporal gyrus and caudate nucleus were shown.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The study of Micalos et al (33) did not show any statistically significant pressure-induced brain activity changes following exercise therapy in a sample of chronic musculoskeletal pain patients. Only group by time trends towards activity changes in the superior temporal gyrus and caudate nucleus were shown.…”
Section: Discussionmentioning
confidence: 81%
“…Two of the included studies applied physical exercise therapy (30,33). Flodin et al (30) included fibromyalgia patients, which were evaluated by restingstate functional connectivity of 6 predefined seed regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an improvement in pain tolerance has been an outcome of aerobic training programs in previously untrained individuals [23][24][25], which the authors attributed predominantly to psychological adaptations to training (although this was not measured). The increased pain tolerance could have arisen as a result of diminished signalling in response to the noxious stimulus [26][27][28], but this desensitisation of the nociceptors is hard to measure and unlikely given that these studies also observed no change in pain threshold. A more likely explanation is that exposure to frequent and unpleasant sensory experiences during aerobic training permits the participants to develop a means of coping and a tolerance to these sensations.…”
Section: This Association Between Pain and Exercise No Doubt Providesmentioning
confidence: 98%
“…Hypoalgesic effects have been shown with exercise duration of 30 min but not at 10 min (Hoffman et al 2004 ). Research on the effect of exercise on pain response is of interest due to evaluating changes in the function of the pain inhibitory system (Micalos et al 2014 ). Understanding the function of the pain inhibitory system is beneficial for improving the prescription of exercise in chronic pain therapy (Carbonell-Baeza et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%